+0  
 
0
288
1
avatar

x + y = 9

-10x + 6y = 6

Guest Aug 4, 2017
 #1
avatar+90088 
+1

 

x + y = 9      →       x  =  9 - y      (1)       note......this isolates x

-10x + 6y = 6     (2)

 

Sub (1)  into (2)

 

-10 ( 9 - y) + 6y  = 6     simplify

 

-90 + 10y + 6y  = 6

 

-90 + 16y  = 6      add 90 to both sides

 

16y = 96     divide both sides by  16

 

y  = 6          and using (1),    x =  9 - 6   =   3

 

 

cool cool cool

CPhill  Aug 4, 2017

8 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.